Diet, Carnitine, and Valproate-Induced Ammonemia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
The effect of a protein-rich meal (45 g protein) before and after L-carnitine (50 mg/kg/day) for 7 days in 11 epileptic children treated with valproate (VPA) was studied in relation to the magnitude and duration of the VPA-induced hyperammonemia at the University of Wisconsin School of Pharmacy and Department of Neurology, Madison, WI.